Design and Implementation of Kalman Filter for Fuel Pipe Damping Test Machine Working Based on Variable Frequency Vibration Principle - Yalcin, Baris Can; Balcilar, Muhammet; Koyun, Ahmet (SAGE PUBLICATIONS LTD, 2017)
Fuel pipes popularly used in automotive industry applications carry fuel from the fuel tank to the engine and work under variable vibrations having different magnitude and frequency parameters due to the engine's rotation frequency and road profile's spontaneous change. Considering that the transfer of the fuel to the engine in the desired way has a crucial importance on the driving performance, any problem that may exist because of the vibrations cannot be acceptable in the pipe assembly. Because of this reason, all manufactured fuel pipes have to be well tested in terms of some industrial standards. The fluid excitement test is a very useful and commonly accepted method in the industry. However, this method produces enormous amount of noise that does not allow to obtain healthy pressure values from the sensors. In this study, Kalman filtering method has been used to interpret the data that have been obtained from the sensors. The usefulness and effectiveness of the proposed Kalman filtering method have been shown and discussed based on the test results.
Keywords: Automation & Control Systems; Instruments & Instrumentation